Keep that magic going in 2015!. Issue 3 (January 2015) - Venditti, Ellen Grady
<x xml:space="preserve">Abstract</x> Greetings and welcome to ASHRM's 35th anniversary year! As I begin my term as president, I acknowledge and appreciate the richness and depth of our organization's history and value the wisdom of our many members and volunteers who have been actively involved in ASHRM from the beginning, as well as those of us who haven't been around that long!